Neuropharmaceutical Properties of Naringin Against Alzheimer’s and Parkinson’s Diseases: - Poudineh, Sahar; Poudineh, Maryam; Ghotbi, Tahere; Azizi, Farnoush; Karami, Nooshin; Zolfaghari , Zahra; Gheisari, Farshid; Hormozi, Mohammad (Galen Medical Journal, 2022)
Neurological complications are considered the leading cause of disability and the second cause of death worldwide. Although the most common neurological disorders affecting a large population are Alzheimer’s (AD) and Parkinson’s diseases (PD), no definitive treatment has been propounded in the clinic. As in recent years, special attention has been paid to medicinal herbal products as one of the ways to meet the challenges of treating diseases. This review study aimed to introduce the naringin neuroprotective effects as an abundant flavonoid in grapes and citrus fruits on the most common neurological disorders, including AD and PD. For this purpose, the specified keywords were searched in PubMed, Web of Science, Scopus, Embase, and Google Scholar, and the results were entered into the study after a concise overview. The findings show naringin can confront neurological disorders through several mechanisms such as modulating stress response pathways, preventing apoptosis, oxidative stress, and neuroinflammation, excessive chelating amounts of metal ions, thereby improving cognitive impairment and memory loss induced by neurological disorders. However, further studies, particularly on human, are critical for the final confirmation of obtained findings.